The Characteristics of Transformative Consumer Research and How it Can Contribute to and Enhance Consumer Psychology. Issue 2 (16th April 2020) - Davis, Brennan; Pechmann, Cornelia (Connie)
Abstract : This article is part of the issue "Transformative Consumer Research": Stornelli et al. (2019): https://doi.org/10.1002/jcpy.1100 Mende et al. (2019): https://doi.org/10.1002/jcpy.1103 Haws et al. (2019): https://doi.org/10.1002/jcpy.1129